Microwave-assisted synthesized M-SnO2 / NH2-Zr-MOFs composite material catalyst as well as preparation method and application thereof

The M-SnO2/NH2-Zr-MOFs composite catalyst was prepared by microwave-assisted synthesis method, which solved the problems of easy deactivation of existing catalysts at high temperatures and low solar energy utilization, and achieved efficient catalyzing of methanol-water liquid phase reforming at low temperatures, thereby improving the activity and stability of the catalyst.

CN119909762APending Publication Date: 2025-05-02GUANGDONG UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510333296.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The catalysts in the existing photocatalytic system are prone to inactivation at high temperatures, have low solar energy utilization, and are easy to recombinate photogenerated carriers, and their stability needs to be improved, making it difficult to effectively solve the challenges of storage and transportation during hydrogen utilization.

Method used

The M-SnO2/NH2-Zr-MOFs composite catalyst was prepared by microwave-assisted synthesis method, and the microwave-assisted single-atom metal was participated in microwave-assisted loading of single-atom metals through a metal organic framework, and microwave-assisted modification of the loaded single-atom metal sites was performed to improve the metal loading and utilization rate, and optimize the electronic structure of the catalyst.

Benefits of technology

It is achieved efficient catalyzing of methanol-water liquid phase reforming at low temperatures (120-140°C), which significantly improves the activity and stability of the catalyst, reduces energy consumption, and extends the service life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119909762A_ABST
    Figure CN119909762A_ABST
Patent Text Reader

Abstract

The invention discloses a microwave-assisted synthesized M-SnO2 / NH2-Zr-MOFs composite material catalyst and a preparation method and application thereof, and belongs to the technical field of catalysts.The preparation method comprises the following steps that 1, a metal source and precursor NH2-Zr-MOFs are mixed in a solvent to be subjected to a microwave-assisted reaction, and a precursor A is obtained; and (2) mixing the precursor A and a tin source in a solvent, and carrying out microwave-assisted reaction again to obtain the M-SnO2 / NH2-Zr-MOFs composite material catalyst. The invention also discloses the catalyst prepared by the preparation method and application of the catalyst in the field of hydrogen production by photothermal synergistic catalysis of methanol-water liquid phase reforming. The unique structural design effectively prolongs the service life of the catalyst, avoids the phenomenon that a traditional catalyst is easy to sinter at high temperature, and enables the catalyst to have wide application prospects in the field of photo-thermal catalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts, and in particular relates to a microwave-assisted synthesized M-SnO2 / NH2-Zr-MOFs composite material catalyst, a preparation method and an application thereof. Background Art

[0002] As an industrial raw material, hydrogen can be widely used in energy, chemical industry, metallurgy, electronics and other fields. The storage and transportation of hydrogen is a challenge. Since hydrogen is difficult to liquefy, high-pressure gas cylinders are usually used to store and transport hydrogen, but this method has low hydrogen storage capacity and greater safety risks. Methanol (CH3OH), as a liquid organic hydrogen storage carrier with a wide source, safe and economical, easy to store and transport, has a high H2 capacity (12.6wt%) and is regarded as an ideal solution to the storage and transportation challenges in hydrogen utilization. Obtaining hydrogen stored in methanol through methanol-water reforming (RMW) can amplify the amount of H2 released per unit of methanol (to 18.8wt%).

[0003] Traditional industrial methanol-water reforming (RMW) hydrogen production requires a reaction temperature of 200-350°C and a reaction pressure greater than 2MPa. The high temperature required for the reaction results in high energy consumption and the generation of CO. In contrast, photocatalytic technology has mild reaction conditions and low energy consumption, but it has problems such as low solar energy utilization, easy recombination of photogenerated carriers, and low hydrogen production rate. Combining light energy and thermal energy for photothermal synergistic catalysis has the following unique advantages: thermal energy enhances the thermal motion of reactants, accelerates mass transfer, and promotes the dissociation of reactants; light energy separates electrons and holes, enhancing redox capacity.

[0004] In the photothermal synergistic catalytic technology, the catalyst plays a vital role. It is not only the core to promote chemical reactions, but also the key to determine the performance of the entire system. At present, the catalysts of the photocatalytic system mainly include traditional photocatalysts such as titanium dioxide (TiO2) and cadmium sulfide (CdS). Although these catalysts have shown certain photocatalytic activity and can drive the redox reactions of organic matter such as methanol, they still face many challenges in practical applications, such as the active sites in the catalyst are easily deactivated at high temperatures, the utilization rate of solar energy is low, the photogenerated carriers are easy to recombine, and the stability needs to be improved. Further improvement is still needed.

[0005] Therefore, how to provide a high-activity, low-energy-consumption photothermal synergistic catalyst to solve the storage and transportation challenges in hydrogen utilization is a technical problem that technicians in this field urgently need to solve. Summary of the invention

[0006] In order to solve the above technical problems, the present invention proposes a microwave-assisted synthesized M-SnO2 / NH2-Zr-MOFs composite material catalyst and a preparation method and application thereof.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] A method for preparing a microwave-assisted synthesized M-SnO2 / NH2-Zr-MOFs composite catalyst comprises the following steps:

[0009] (1) mixing a metal source and a precursor NH2-Zr-MOFs (amino-modified zirconium-based metal-organic framework) in a solvent for microwave-assisted reaction to obtain a precursor A;

[0010] (2) The precursor A is mixed with a tin source in a solvent and subjected to a microwave-assisted reaction again to obtain the M-SnO2 / NH2-Zr-MOFs composite catalyst (M is the corresponding metal in the metal source).

[0011] Beneficial effects: The catalyst provided by the present invention is obtained by microwave-assisted loading of single-atom metals through a metal-organic framework (MOF), and then microwave-assisted modification of the loaded single-atom metal sites. First, the present invention prepares NH2-Zr-MOFs with -OH / OH2 defects in Zr6-oxo, and then uses a microwave-assisted method to load single atoms onto the SBUs of NH2-Zr-MOFs. The microwave-assisted loading method greatly increases the metal loading amount; finally, the single atoms loaded onto SBUs (secondary building units) are modified using a microwave-assisted method, and the prepared M-SnO2 / NH2-Zr-MOFs composite catalyst provides abundant sites for the reaction while also facilitating the separation of photogenerated electrons and holes; the introduction of SnO2 regulates the electronic structure of the metal sites, can optimize the adsorption and electron transfer with the reactants, and shows excellent photothermal catalytic methanol-water phase reforming hydrogen production performance.

[0012] Preferably, the preparation method of the precursor NH2-Zr-MOFs in step (1) comprises the following steps:

[0013] ZrCl4 and 2-aminoterephthalic acid are added to DMF (N,N-dimethylformamide) and mixed evenly, and then acetic acid and H2O are added. The resulting mixture is reacted at 120°C for 24 hours. After the reaction is completed, it is cooled and post-treated to obtain the precursor NH2-Zr-MOFs.

[0014] The post-treatment includes the following steps: repeatedly washing and collecting solids by centrifugation for 3 times, immersing the solids collected by centrifugation in MeOH (methanol) to exchange DMF for 24 hours, continuing to repeatedly wash with MeOH and collect solids by centrifugation for 3 times, and obtaining the precursor NH2-Zr-MOFs after drying.

[0015] Beneficial effects: The introduction of acetic acid regulator causes -OH / OH2 defects in Zr6-oxo (zirconium oxygen cluster) of NH2-Zr-MOFs, which facilitates microwave-assisted loading of Ni single atoms. The introduction of Ni single atoms provides abundant adsorption sites for the reaction, while promoting the transfer of photoexcited electrons from ligands to metal clusters, avoiding the recombination of photogenerated electron-hole pairs and improving the utilization rate of sunlight; in addition, the microwave-assisted introduction of SnO2 avoids the agglomeration of SnO2, forming highly dispersed nanoclusters, and the introduction of SnO2 regulates the electronic structure of the metal M single atom sites, which can optimize the adsorption and electron transfer with the reactants, and can achieve the technical effect of efficient hydrogen production by photothermal catalytic methanol-water liquid phase reforming at low temperature (120-140°C).

[0016] Preferably, the mass ratio of the precursor NH2-Zr-MOFs to the metal source in step (1) is 1:5.

[0017] Preferably, the metal source in step (1) is selected from one of a nickel source, a copper source and a cobalt source.

[0018] Optionally, the nickel source is NiCl2·6H2O or NiCl2; the copper source is CuCl2; and the cobalt source is CoCl2·6H2O.

[0019] Beneficial effects: Ni, Cu and Co in the present invention, as transition metals, can present a variety of chemical states through regulation, so that they can flexibly accept or provide electrons in the reaction to adapt to different reaction requirements; the unfilled d orbital enables the transition metal to form a variety of chemical bonds with the reactants, enhancing the interaction with the reactants. Selecting cheap Ni, Cu and Co as metal sources not only provides active sites for the reaction but also promotes the separation of photogenerated carriers and holes. At the same time, Ni, Cu and Co are cheaper than transition metals such as Pt and Pd, which can effectively reduce the cost of the catalyst.

[0020] Optionally, the solvent in step (1) is acetonitrile.

[0021] Preferably, the first microwave-assisted reaction comprises the following steps: heating to 85° C. under a microwave condition of 150 W for 30 min.

[0022] Preferably, the second microwave-assisted reaction comprises the following steps: heating to 80° C. under a microwave condition of 150 W for 30 min.

[0023] Beneficial effects: Compared with the conventional hydrothermal method which takes 12 hours to react, the microwave-assisted method in the present invention can shorten the reaction time to 30 minutes, greatly improving the reaction efficiency. In addition, the microwave-assisted method has a non-thermal effect of microwaves which can strengthen the interaction between single atoms and SnO2, playing an important role in optimizing the electronic structure of single atoms.

[0024] Preferably, the solvent in step (2) is N,N-dimethylformamide.

[0025] Preferably, the mass ratio of the precursor A to the tin source in step (2) is 1:0.75.

[0026] Preferably, the tin source is SnCl2·2H2O or SnCl2.

[0027] The present invention also discloses a microwave-assisted synthesized M-SnO2 / NH2-Zr-MOFs composite material catalyst prepared by the above preparation method.

[0028] The present invention also discloses an application of a microwave-assisted synthesized M-SnO2 / NH2-Zr-MOFs composite material catalyst in the field of photothermal synergistic catalytic methanol-water liquid phase reforming hydrogen production.

[0029] Beneficial effect: The present invention reduces the energy consumption in the reaction process by means of photothermal synergistic effect, and utilizes sunlight to promote redox reaction, so that the catalytic activity can be maintained even at low temperature, thereby realizing low energy consumption and stable hydrogen production at low temperature.

[0030] A method for producing hydrogen by photothermal catalytic methanol-water liquid phase reforming comprises the following steps:

[0031] The M-SnO2 / NH2-Zr-MOFs composite material catalyst, methanol, water and alkali are mixed and reacted to obtain hydrogen.

[0032] Preferably, the base is potassium hydroxide (KOH); the molar ratio of methanol to water is 1:1-3; the reaction is carried out under anaerobic, light and heating conditions, and the heating temperature is 120-210°C.

[0033] Compared with the prior art, the present invention has the following advantages and technical effects:

[0034] First, the metal atoms (Ni, Cu or Co) are highly dispersed in the carrier in the form of single atoms, which significantly improves the atomic utilization rate. Secondly, the uniform dispersion of SnO2 nanoparticles is ensured through microwave-assisted synthesis technology. At the same time, the introduction of SnO2 effectively adjusts the electronic structure of the metal site, thereby optimizing the adsorption performance and electron transfer efficiency between the catalyst and the reactant. Among them, the metal single atom serves as the active center of photothermal catalysis. Its unique single-atom dispersion characteristics enable each metal atom to serve as an independent active site, maximizing the utilization rate of metal atoms. In addition, the single-atom active center has a highly uniform geometry and electronic structure, which can provide a consistent catalytic path, effectively inhibit the occurrence of side reactions, and significantly improve the reaction selectivity.

[0035] The M-SnO2 / NH2-Zr-MOFs composite catalyst prepared by the microwave-assisted synthesis technology of the present invention has multiple advantages: first, the present invention realizes the synergistic utilization of thermal energy and solar energy, significantly improves the reaction rate and catalytic efficiency through the photothermal synergistic effect, and the introduction of light energy effectively reduces the overall energy consumption, which is in line with the concept of green chemistry. In addition, the present invention expands the applicable conditions of the catalyst, and can realize the efficient reaction of methanol-water liquid phase reforming hydrogen production under relatively mild temperature conditions (120-140°C), significantly improves the reaction selectivity by inhibiting side reactions, and the unique structural design of the present invention effectively prolongs the service life of the catalyst, avoiding the sintering phenomenon that is easy to occur in traditional catalysts at high temperatures. These characteristics make the catalyst have broad application prospects in the field of photothermal catalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0037] Figure 1 XRD patterns of the NH2-Zr-MOFs, Ni / NH2-Zr-MOFs and Ni-SnO2 / NH2-Zr-MOFs composite catalysts in Example 1;

[0038] Among them, a is the XRD spectrum of NH2-Zr-MOFs, b is the XRD spectrum of Ni / NH2-Zr-MOFs, and c is the XRD spectrum of Ni-SnO2 / NH2-Zr-MOFs composite catalyst;

[0039] Figure 2 The scanning electron microscope images of the NH2-Zr-MOFs, Ni / NH2-Zr-MOFs and Ni-SnO2 / NH2-Zr-MOFs composite catalysts in Example 1;

[0040] Among them, a is NH2-Zr-MOFs, b is Ni / NH2-Zr-MOFs, and c is Ni-SnO2 / NH2-Zr-MOFs composite catalyst;

[0041] Figure 3 This is a high-magnification transmission electron microscopy image of the Ni-SnO2 / NH2-Zr-MOFs composite catalyst in Example 1.

[0042] Parts a and g are the overall morphology and local morphology of the Ni-SnO2 / NH2-Zr-MOFs composite catalyst, respectively; parts b to f are the distribution of N, O, Zr, Ni, and Sn elements on the surface of the Ni-SnO2 / NH2-Zr-MOFs composite catalyst, respectively; and part h is the lattice fringes of SnO2 nanoparticles in the Ni-SnO2 / NH2-Zr-MOFs composite catalyst.

[0043] Figure 4 This is a comparison chart of the photothermal catalytic methanol-water liquid phase reforming hydrogen production performance of NH2-Zr-MOFs, Ni / NH2-Zr-MOFs and Ni-SnO2 / NH2-Zr-MOFs composite catalysts in Example 1;

[0044] Figure 5 This is a performance diagram of hydrogen production from photothermal catalytic methanol-water liquid phase reforming of the Ni-SnO2 / NH2-Zr-MOFs composite catalyst in Example 1 at low temperature. DETAILED DESCRIPTION

[0045] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0047] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources;

[0048] Unless otherwise specified, the room temperature or normal temperature in the embodiments of the present invention refers to 25±3°C.

[0049] Example 1

[0050] A method for preparing a microwave-assisted synthesized Ni-SnO2 / NH2-Zr-MOFs composite catalyst specifically comprises the following steps:

[0051] (1) Preparation of NH2-Zr-MOFs

[0052] 186mg ZrCl4 (0.8mmol) and 145mg 2-aminoterephthalic acid (0.8mmol) were added to 50mL DMF, stirred and mixed evenly, and then ultrasonicated for 15 minutes, and then 6mL acetic acid and 500μL H2O were added under continuous stirring. The resulting mixture was transferred to a 100ml hydrothermal kettle with a Teflon liner and kept in a constant temperature blast drying oven at 120℃ for 24h. After drying, the temperature was lowered to room temperature and the solid was collected by centrifugation. The solid was washed with DMF three times and collected by centrifugation three times. The solid collected by centrifugation was soaked in MeOH to exchange DMF for 24h, and then washed with MeOH and collected by centrifugation three times. Finally, the precursor NH2-Zr-MOFs was obtained after vacuum drying at 60℃.

[0053] (2) Preparation of Ni / NH2-Zr-MOFs composites

[0054] 120 mg of NH2-Zr-MOFs and 600 mg of NiCl2·6H2O were added to a 30 mL microwave container, and 18 mL of acetonitrile was added to obtain a mixture. The mixture was rapidly heated to 85°C by a microwave reactor and maintained at this temperature for 30 min while continuously stirring. After the reaction was completed, it was cooled to room temperature, and the solid was separated by centrifugation, and the solid was repeatedly washed with DMF and collected by centrifugation 3 times, and then washed with MeCN (acetonitrile) and collected by centrifugation 3 times, and finally Ni / NH2-Zr-MOFs were obtained after vacuum drying at 60°C.

[0055] Element content analysis showed that the Ni content in the Ni / NH2-Zr-MOFs composite material was 6.73wt%.

[0056] (3) Preparation of Ni-SnO2 / NH2-Zr-MOFs composite catalyst

[0057] 100 mg of Ni / NH2-Zr-MOFs and 75 mg of SnCl2·2H2O were added to a 30 mL microwave container, and 10 mL of N,N-dimethylformamide was added to obtain a mixture. The mixture was rapidly heated to 80°C by a microwave reactor and maintained at this temperature for 30 min while continuously stirring. After cooling to room temperature, the solid was separated by centrifugation. The solid was washed with DMF and collected by centrifugation 3 times, then washed with MeOH and collected by centrifugation 3 times, and finally dried in vacuum at 60°C to obtain the Ni-SnO2 / NH2-Zr-MOFs composite catalyst.

[0058] Element content analysis showed that the Ni content in the Ni-SnO2 / NH2-Zr-MOFs composite catalyst was 3.75wt% and the Sn content was 0.99wt%.

[0059] Example 2

[0060] A method for preparing a microwave-assisted synthesis Co-SnO2 / NH2-Zr-MOFs composite catalyst is different from Example 1 only in that the type of nickel source in step (2) is changed, and NiCl2·6H2O is replaced by an equal mass of CoCl2·6H2O. The remaining process steps and parameters are the same as those in Example 1.

[0061] Example 3

[0062] A method for preparing a Cu-SnO2 / NH2-Zr-MOFs composite catalyst by microwave-assisted synthesis, which differs from Example 1 only in that the type of nickel source in step (2) is changed, and NiCl2·6H2O is replaced by an equal mass of CuCl2. The remaining process steps and parameters are the same as those in Example 1.

[0063] Comparative Example 1

[0064] A method for preparing a microwave-assisted synthesis Ni / NH2-Zr-MOFs composite catalyst is different from Example 1 in that step (3) is omitted to prepare a material not modified by SnO2. Other parameters and operations are the same as in Example 1.

[0065] Comparative Example 2

[0066] A method for preparing a microwave-assisted synthesized Co / NH2-Zr-MOFs composite catalyst is different from Example 2 in that step (3) is omitted to prepare a material that is not modified by SnO2. Other parameters and operations are the same as in Example 2.

[0067] Comparative Example 3

[0068] A method for preparing a Cu / NH2-Zr-MOFs composite catalyst by microwave-assisted synthesis is different from Example 3 in that step (3) is omitted to prepare a material not modified by SnO2. Other parameters and operations are the same as those in Example 3.

[0069] Comparative Example 4

[0070] A method for preparing a Ni-SnO2 / NH2-Zr-MOFs composite catalyst synthesized by oil bath heating, which is different from Example 1 in that the heating method in step (3) is changed from the process of rapidly heating the mixture to 80°C by a microwave reactor and maintaining the mixture at the temperature for 30 minutes to heating the mixture to 80°C by an oil bath and maintaining the mixture at the temperature for 12 hours. Other parameters and operations are the same as those in Example 1.

[0071] Comparative Example 5

[0072] A method for preparing a microwave-assisted synthesis Ni / NH2-Zr-MOFs composite catalyst is different from Example 1 in that acetic acid is not added in step (1). The remaining process steps and parameters are the same as those in Example 1.

[0073] Comparative Example 6

[0074] A method for preparing a Ni-SnO2 / NH2-Zr-MOFs composite catalyst, which differs from Example 1 in that metal Sn is loaded first and then metal Ni is loaded, specifically: the type of metal salt in step (2) is changed, NiCl2·6H2O is replaced by an equal mass of SnCl2·2H2O; the type of metal salt in step (3) is changed, SnCl2·2H2O is replaced by an equal mass of NiCl2·6H2O. The remaining process steps and parameters are the same as those in Example 1.

[0075] Element content analysis shows that the Ni content in the Ni-SnO2 / NH2-Zr-MOFs composite catalyst is 0.40wt% and the Sn content is 12.6wt%.

[0076] Technical Effects

[0077] 1. The Ni-SnO2 / NH2-Zr-MOFs composite catalyst prepared in Example 1 was characterized and its photothermal catalytic performance was tested.

[0078] The crystal structure of the product of Example 1 was analyzed by X-ray diffractometer.

[0079] Figure 1The XRD patterns of NH2-Zr-MOFs, Ni / NH2-Zr-MOFs and Ni-SnO2 / NH2-Zr-MOFs composite catalysts in Example 1. Wherein, a represents the XRD pattern of NH2-Zr-MOFs, b represents the XRD pattern of Ni / NH2-Zr-MOFs, and c represents the XRD pattern of Ni-SnO2 / NH2-Zr-MOFs composite catalyst. It can be seen that NH2-Zr-MOFs, Ni / NH2-Zr-MOFs and Ni-SnO2 / NH2-Zr-MOFs composite materials all have good crystallinity; the characteristic peak of Ni is not observed in the XRD diffraction pattern of Ni / NH2-Zr-MOFs and there is no obvious difference with the XRD pattern of NH2-Zr-MOFs, indicating that Ni is highly dispersed and no agglomeration occurs; the XRD pattern of the Ni-SnO2 / NH2-Zr-MOFs composite catalyst is not significantly different from the XRD patterns of NH2-Zr-MOFs and Ni / NH2-Zr-MOFs, indicating that the Ni-SnO2 / NH2-Zr-MOFs composite material maintains the structure of NH2-Zr-MOFs, and the absence of the diffraction peak of SnO2 indicates that SnO2 is highly dispersed and does not agglomerate into clusters larger than 10nm, and the catalyst has been successfully prepared. The XRD patterns of the product obtained in step 2 of Examples 2 to 3 and the final composite material obtained are basically consistent with those of Example 1.

[0080] Figure 2 The scanning electron microscope images of NH2-Zr-MOFs, Ni / NH2-Zr-MOFs and Ni-SnO2 / NH2-Zr-MOFs composite catalysts in Example 1 are shown. Among them, a is NH2-Zr-MOFs, b is Ni / NH2-Zr-MOFs, and c is Ni-SnO2 / NH2-Zr-MOFs composite catalyst. It can be seen that the prepared NH2-Zr-MOFs has an octahedral structure. After the introduction of Ni single atoms, the octahedral structure of the Ni / NH2-Zr-MOFs composite material in (b) is well maintained. After the introduction of SnO2, no SnO2 is observed in (c), indicating that Ni-SnO2 is uniformly dispersed in the pores of NH2-Zr-MOFs without agglomeration. The SEM images of the composite materials obtained in Examples 2 to 3 are basically consistent with those in Example 1, and the structure of the composite material remains basically unchanged.

[0081] Figure 3The high-magnification transmission electron microscope image of the Ni-SnO2 / NH2-Zr-MOFs composite catalyst in Example 1. Parts a and g are the overall morphology and local morphology of the Ni-SnO2 / NH2-Zr-MOFs composite catalyst, respectively; parts b to f are the distribution of N, O, Zr, Ni, and Sn elements on the surface of the Ni-SnO2 / NH2-Zr-MOFs composite catalyst, respectively; and part h is the lattice stripes of SnO2 nanoparticles in the Ni-SnO2 / NH2-Zr-MOFs composite catalyst. It can be seen that the Ni and Sn elements are evenly distributed on the surface of the Ni-SnO2 / NH2-Zr-MOFs composite catalyst, wherein the Sn element is more sparsely distributed than the Ni element, because the loading amount of Sn is lower than that of Ni. The diameter of the SnO2 nanoparticles is 2 to 5 nanometers, and the exposed crystal planes are (211) and (210). This is mainly because the microwave introduction of SnO2 in the Ni / NH2-Zr-MOFs composite material can regulate the size of the nanoparticles, avoiding the excessive growth of SnO2 nanoparticles to block the pores of the catalyst. At the same time, the exposed crystal faces of the SnO2 nanoparticles of the Ni-SnO2 / NH2-Zr-MOFs in the present invention are different from the (101) and (110) exposed by the general SnO2 nanoparticles, indicating that the microwave introduction of SnO2 in the Ni / NH2-Zr-MOFs composite material has a regulating effect on the crystal faces of the SnO2 nanoparticles.

[0082] 2. The NH2-Zr-MOFs obtained in Example 1 and the composite materials obtained in Examples 1 to 3 and Comparative Examples 1 to 6 were tested for hydrogen production by photothermal catalytic methanol-water liquid phase reforming.

[0083] Photothermal catalytic methanol-water liquid phase reforming hydrogen production is carried out in a photothermal reactor and heated by a heating furnace with a magnetic stirring device. The specific test method is as follows:

[0084] The photothermal catalytic methanol-water liquid phase reforming hydrogen production reaction is carried out in a stainless steel high-pressure photothermal autoclave (CEL-HPR50, 50mL) having a quartz lining, a magnetic stirrer and a visible sapphire window. Under the optimal reaction conditions, the NH2-Zr-MOFs obtained in Example 1 and the composite materials obtained in Examples 1 to 3 and Comparative Examples 1 to 5 are respectively activated under vacuum at 150°C and transferred to the photothermal reactor lining containing 10mL of a MeOH / H2O mixed solution (nMeOH / nH2O=1) and 5wt% KOH; the sealed reactor is repeatedly filled and discharged with 2MPa N2 three times, and then reacted at 210°C for 80min under a 2MPa N2 atmosphere, irradiation with a 300W Xe lamp (CEL-HXF300-T3) and a stirring speed of 500rpm. After the reaction, the gas products in the headspace of the autoclave are analyzed by GC chromatography to determine the amount of H2 produced, and compared with the relevant data under no light conditions. The test results are as follows Figure 3 As shown in Table 1. By adjusting the above reaction temperature alone, the hydrogen production rate of the product at low temperature (120-210°C) was tested. The test results are shown in Figure 5 shown.

[0085] Table 1 Performance data of the photothermal catalytic methanol-water liquid phase reforming hydrogen production test of the NH2-Zr-MOFs in Example 1, the composite materials obtained in Examples 1 to 3 and Comparative Examples 1 to 6

[0086] sample <![CDATA[Photothermal catalytic hydrogen production rate μmol / g cat / h]]> <![CDATA[NH2-Zr-MOFs]]> <![CDATA[3.00×10 4 ]]> Example 1 <![CDATA[2.93×10 5 ]]> Example 2 <![CDATA[1.04×10 5 ]]> Example 3 <![CDATA[1.32×10 5 ]]> Comparative Example 1 <![CDATA[8.14×10 4 ]]> Comparative Example 2 <![CDATA[5.24×10 4 ]]> Comparative Example 3 <![CDATA[5.90×10 4 ]]> Comparative Example 4 <![CDATA[1.06×10 5 ]]> Comparative Example 5 <![CDATA[4.51×10 4 ]]> Comparative Example 6 <![CDATA[9.49×10 4 ]]>

[0087] It can be seen from Table 1 that the Ni-SnO2 / NH2-Zr-MOFs composite catalyst in Example 1, the Co-SnO2 / NH2-Zr-MOFs composite catalyst in Example 2 and the Cu-SnO2 / NH2-Zr-MOFs composite catalyst in Example 3 have 9.77, 3.47 and 4.4 times higher photo-thermal catalytic hydrogen production rates than the carrier NH2-Zr-MOFs, among which the performance of the composite material loaded with metal single atom Ni is most significantly improved. This is mainly because the carrier NH2-Zr-MOFs lacks metal active sites. After the introduction of microwave-assisted SnO2-modified metal single atoms into the carrier NH2-Zr-MOFs, it not only provides active sites for the reaction but also promotes the separation of photogenerated carriers and holes. Compared with the composite catalysts modified by microwave-assisted SnO2 in Examples 1, 2 and 3, The photo-thermal catalytic hydrogen production rate of the composite catalysts not modified by SnO2 in Examples 1, 2, and 3 is significantly improved, among which the photo-thermal catalytic hydrogen production rate of the Ni-SnO2 / NH2-Zr-MOFs composite catalyst is 3.6 times that of the Ni / NH2-Zr-MOFs composite catalyst not modified by microwave-assisted SnO2 in Example 1. This is mainly because the SnO2 introduced in the present invention adjusts the electronic structure of the metal single atom site, can optimize the adsorption and electron transfer with the reactants, and prolong the life of the electron-hole pairs; in Example 4, the photo-thermal catalytic hydrogen production rate of the composite catalyst using the hydrothermal method to introduce SnO2 is significantly lower than that of the composite catalyst modified by microwave-assisted SnO2 in Example 1. This is mainly because the non-thermal effect of microwaves strengthens the interaction between single atoms and SnO2, which plays an important role in optimizing the electronic structure of metal single atoms. The photo-thermal catalytic hydrogen production rate of the composite catalyst in Comparative Example 5 is significantly lower than that of the composite catalyst in Example 1. This is mainly because the -OH / OH2 defects of Zr6-oxo (zirconium oxygen cluster) in NH2-Zr-MOFs are greatly reduced, which makes it difficult for metal single atoms to be loaded onto NH2-Zr-MOFs and cannot provide sufficient active sites for the reaction. The photo-thermal catalytic hydrogen production rate of the composite catalyst in Comparative Example 6 is only one-third of that of the composite catalyst in Example 1. This is mainly because Comparative Example 6 first loads metal Sn and then loads metal Ni, resulting in a Ni loading of only 0.4wt%, which is much less than the Ni-SnO2 / NH2-Zr-MOFs composite catalyst in Example 1, and the active sites are also reduced accordingly. At the same time, loading metal Sn first weakens the interaction between Sn and Ni, so the photo-thermal catalytic hydrogen production rate is significantly reduced.

[0088] Figure 4This is a comparison chart of the photothermal catalytic methanol-water liquid phase reforming hydrogen production performance of NH2-Zr-MOFs, Ni / NH2-Zr-MOFs and Ni-SnO2 / NH2-Zr-MOFs composite catalysts in Example 1.

[0089] Figure 4 The results show that the hydrogen production rate of Ni-SnO2 / NH2-Zr-MOFs composite material under photothermal catalysis conditions reached 293620.70 μmol·g -1 ·h -1 , which is 13.3 times that under thermal catalytic conditions; the photothermal hydrogen production rate of Ni-SnO2 / NH2-Zr-MOFs composite material is about 10 times that of its original NH2-Zr-MOFs and 3.6 times that of Ni / NH2-Zr-MOFs. This is mainly because light energy excites the catalyst to produce highly active electron-hole pairs, while thermal energy accelerates molecular thermal motion and provides additional activation energy, and the two work together to reduce the reaction energy barrier; the thermal effect can promote the separation of photogenerated carriers and reduce electron-hole recombination (the main bottleneck of traditional photocatalysis). Ni-SnO2 / NH2-Zr-MOFs composite material introduces Ni single atoms into the carrier to obtain metal active sites in the form of isolated single atoms. Almost every metal atom is exposed on the surface and participates in the catalytic reaction, avoiding the waste of internal atoms being "buried" in traditional catalysts; the introduction of SnO2 further optimizes the electronic structure of Ni single atoms, which can optimize the adsorption and electron transfer with reactants and prolong the life of electron-hole pairs. Light energy excites the catalyst to produce highly active electron-hole pairs, while thermal energy accelerates molecular thermal motion and provides additional activation energy, and the two work together to reduce the reaction energy barrier. This shows that the photothermal catalytic performance of methanol hydrogen production of Ni-SnO2 / NH2-Zr-MOFs composite catalyst can indeed be significantly improved.

[0090] Figure 5 The photothermal catalytic methanol-water liquid phase reforming hydrogen production performance diagram of the Ni-SnO2 / NH2-Zr-MOFs composite catalyst in Example 1 at 120-210°C. It can be seen that the Ni-SnO2 / NH2-Zr-MOFs composite catalyst broadens the applicable temperature of the reaction, and the photothermal catalytic hydrogen production rate at 120°C is still 326.6μmol·g -1 ·h -1 , achieving the synergistic utilization of thermal energy and solar energy, reducing the reaction energy consumption, and conforming to the concept of green chemistry. This is mainly because the photothermal synergistic effect reduces the reaction energy barrier, making the temperature required to start the reaction lower.

[0091] In summary, the M-SnO2 / NH2-Zr-MOFs composite material prepared by the present invention has abundant metal atom active sites, and the application of microwave-assisted synthesis increases the metal loading and the utilization rate of metal atom M. The introduction of metal atom active sites can promote adsorption and activation with reactants. Among them, metal single atoms are the active centers of photothermal catalysis, and the catalytic activity of metal single atoms modified by SnO2 is significantly improved. In addition, the microwave non-thermal effect strengthens the interaction between single atoms and SnO2, which plays an important role in optimizing the electronic structure of single atoms. The microwave-assisted synthesized M-SnO2 / NH2-Zr-MOFs composite catalyst of the present invention can combine thermal energy and solar energy, realize the synergistic effect of light and heat to increase the reaction rate; the introduction of light reduces the overall energy consumption; reduces side reactions and improves selectivity; prolongs the catalyst life and avoids high-temperature sintering; expands the applicable reaction conditions, and can achieve the technical effect of efficient hydrogen production by photothermal catalytic methanol-water liquid phase reforming hydrogen production at low temperature (120-140°C).

[0092] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a microwave-assisted synthesized M-SnO2 / NH2-Zr-MOFs composite catalyst, characterized in that: The following steps are involved: (1) mixing a metal source and a precursor NH2-Zr-MOFs in a solvent to perform a first microwave-assisted reaction to obtain a precursor A; (2) The precursor A is mixed with a tin source in a solvent to carry out a second microwave-assisted reaction to obtain the M-SnO2 / NH2-Zr-MOFs composite catalyst.

2. The method for preparing a microwave-assisted synthesized M-SnO2 / NH2-Zr-MOFs composite catalyst according to claim 1, characterized in that: The mass ratio of the precursor NH2-Zr-MOFs to the metal source in step (1) is 1:

5.

3. The method for preparing a microwave-assisted synthesized M-SnO2 / NH2-Zr-MOFs composite catalyst according to claim 2, characterized in that: The preparation method of the precursor NH2-Zr-MOFs comprises the following steps: ZrCl4 and 2-aminoterephthalic acid are added to DMF and mixed evenly, and then acetic acid and H2O are added. The resulting mixture is reacted at 120°C for 24 hours. After the reaction is completed, it is cooled and post-treated to obtain the precursor NH2-Zr-MOFs.

4. The method for preparing a microwave-assisted synthesized M-SnO2 / NH2-Zr-MOFs composite catalyst according to claim 2, characterized in that: The metal source is selected from one of a nickel source, a copper source and a cobalt source.

5. The method for preparing a microwave-assisted synthesized M-SnO2 / NH2-Zr-MOFs composite catalyst according to claim 1, characterized in that: The first microwave-assisted reaction comprises the following steps: heating to 85° C. under a microwave condition of 150 W for 30 min.

6. The method for preparing a microwave-assisted synthesized M-SnO2 / NH2-Zr-MOFs composite catalyst according to claim 1, characterized in that: The second microwave-assisted reaction comprises the following steps: heating to 80° C. under a microwave condition of 150 W for 30 min.

7. The method for preparing a microwave-assisted synthesized M-SnO2 / NH2-Zr-MOFs composite catalyst according to claim 1, characterized in that: The mass ratio of the precursor A to the tin source is 1:0.

75.

8. A microwave-assisted synthesis of M-SnO2 / NH2-Zr-MOFs composite catalyst, characterized in that: The method is described in any one of claims 1 to 7.

9. Application of a microwave-assisted synthesized M-SnO2 / NH2-Zr-MOFs composite material catalyst as described in claim 8 in the field of photothermal synergistic catalytic methanol-water liquid phase reforming hydrogen production.

10. A method for producing hydrogen by photothermal catalytic methanol-water liquid phase reforming, characterized in that: The following steps are involved: The M-SnO2 / NH2-Zr-MOFs composite material catalyst according to claim 8, methanol, water and alkali are mixed and reacted to obtain hydrogen.

Citation Information

Cited By

  • Surface-modified Cu-based catalyst, preparation method thereof and application of surface-modified Cu-based catalyst in preparation of ethanol through CO hydrogenation

    CN120939996A